DNA barcoding of the genus Apaidia Hampson, 1900 for species delimitation from Western Mediterranean fauna (Lepidoptera, Erebidae) - Ortiz, A. S.; Rubio, R. M.; Guerrero, J. J.; Garre, M.; Yela, J. L. (Zootaxa, 2023)
The genus Apaidia Hampson, 1900 is a relict Western Mediterranean genus in the South-western part of Europe and the North-western areas of the Mediterranean Africa comprising so far three species, Apaidia rufeola (Rambur, 1832), Apaidia mesogona (Godart, [1824]) and Apaidia barbarica Legrand, 1939. According to the examined material, COI mitochondrial DNA sequences and adult morphology integration supports the existence of three main lineages of Apaidia with sequence divergence rates of approximately 4.5%, which are within the range reported for other well-defined insect species. In addition, we recovered three different BINS, suggesting the presence of different species with unique and specific identifier for A. mesogona (AEC6797), A. rufeola (AEI9539), and the Iberian-Balearic A. barbarica (AEI9540). This study contributes to a better understanding of the taxonomy of the genus Apaidia and challenges future revision of this genus in Northern Africa, as well as the presence of the Apaidia species in Western Mediterranean islands and populations located in Italy.